Strategic Responses to Algorithmic Recommendations: Evidence from Hotel Pricing - Daniel Garcia; Juha Tolvanen; Alexander K. Wagner (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the interaction between algorithmic advice and human decisions using high-resolution hotel-room pricing data. We document that price setting frictions, arising from adjustment costs of human decision makers, induce a conflict of interest with the algorithmic advisor. A model of advice with costly price adjustments shows that, in equilibrium, algorithmic price recommendations are strategically biased and lead to suboptimal pricing by human decision makers. We quantify the losses from the strategic bias in recommendations using as structural model and estimate the potential benefits that would result from a shift to fully automated algorithmic pricing.
Keywords: D22; D83; L13; 330; advice; algorithmic recommendations; human decisions; adjustment cost; delegation